Poxvirus infection in house finches (Haemorhous mexicanus): Genome sequence analysis and patterns of infection in wild birds. Issue 5 (10th May 2022) - McGraw, Kevin J; Aguiar de Souza Penha, Victor; Drake, Dean J; Kraberger, Simona; Varsani, Arvind
Abstract: Poxviruses (family: Poxviridae ) infect many avian species, causing several disease outcomes, the most common of which are proliferative lesions on the legs, feet, and/or head. Few avian studies of poxvirus to date have combined molecular and ecological analyses to obtain a more comprehensive understanding of the identity and distribution of the disease in a population. Here, we describe patterns of poxvirus infection in an urban population of house finches ( Haemorhous mexicanus ) in Arizona (USA) and use high‐throughput sequencing to determine the genome sequence of the virus. We found that poxvirus prevalence, based on visual identification of pox lesions, was 7.2% (17 infected birds out of a total of 235 sampled) in our population during summer 2021. Disease severity was low; 14 of the 17 infected birds had a single small lesion on the skin overlaying the eye, leg, and ear canal. All but two lesions were found on the feet; one bird had a lesion on the eye and the other in the ear opening. We also investigated possible temporal (i.e., date of capture) and biological correlates (e.g., age, sex, body condition, degree of infection with coccidian endoparasites) of poxvirus infection in urban‐caught house finches during this time but found that none of these significantly correlated with poxvirus presence/absence. Two complete poxvirus genomes were determined from two infected birds. These genomes are ∼354, 000 bp and share 99.7% similarity with each other, and 82% with a canarypox virus genome, the most closely related avipoxvirus. This novel finchpox virus is the first to be reported in house finches and has a similar genome organization to other avipoxviruses.